Sexual Responses Are Facilitated by High-Order Contextual Cues in Females but Not in Males. (21st March 2018) - Ponseti, Jorge; Dähnke, Kim; Fischermeier, Leona; Gerwinn, Hannah; Kluth, Amelie; Müller, Jens; Vogel, Susanne; Stirn, Aglaja
Sexual responses are thought to be controlled by a brain module called the sexual module. Sexual strategies of males and females vary to a great extent, and sexual responses of males and females may be affected by their sexual strategies. However, the current view of the sexual module is that of a unisex module. This might be questionable since brain modules are defined as evolved cognitive mechanisms to solve adaptive problems which are different for males and females. We hypothesize that the sexual module responds differently in the presence of complex (high-order) contextual cues that are related to gender-dimorphic sexual strategies in males and females. We conducted a priming experiment in which stimuli related to sexual strategies were disentangled from their sexual meaning. Nonsexual priming pictures related to either economic resources or social interactions preceded a sexual-target picture in order to test whether the primes were able to modulate the subjective sexual response to the sexual target. In a control condition, priming pictures without relation to mating preferences but with similar emotional impact were presented. In males, sexual responses were similar in the experimental and control conditions. In females, however, primes related to economic resources or social interactions modulated sexual arousal significantly more than the control primes. Our findings suggest that brain modules dedicated to process the experimental primes were functionally connected with the sexual module in females more than in males, making females' sexual responses more prone to the impact of high-order cultural cues than males' sexual responses. A gender-dimorphic connectivity of the sexual module may be the way in which gender-dimorphic sexual strategies are implemented in the human mind.